Chaucer Fabliaux as Analogues - Hertog, Erik (Mediaevalia Lovaniensia - Series 1/Studia, 1991)
The presence of so many fabliaux in Chaucer's Canterbury Tales is intriguing in its own right, given the fact that there are no real fabliaux in Middle English befor Chaucer. But these stories are also interesting as instances of a concept and practice thas has received little critical attention so far, namely 'analogy', the writing and, above all, recognition of 'similar' stories. How to account for the literary practice that enables us to perceive stories as similar, c.q. analogous? This original study sets out to explore this phenomenon, first tentatively vis-